Early tracking or finally leaving? Determinants of early study success in first-year university students. Issue 4 (1st October 2016) - Brouwer, Jasperina; Jansen, Ellen; Hofman, Adriaan; Flache, Andreas
Abstract: Two theoretical approaches underlie this investigation of the determinants of early study success among first-year university students. Specifically, to extend Walberg's educational productivity model, this study draws on the expectancy-value theory of achievement motivation in a contemporary university context. The survey data came from 407 first-year students, and the measure of early study success reflects the weighted grade point average at two moments during their first semester. A path model reveals that the proposed extended educational productivity framework explains early study success well. The operationalised educational productivity factors (age, prior achievement, psychosocial environment, programme satisfaction, study skills) and achievement motivation (expectancy) all relate to early study success, directly or indirectly through expectancy and self-study. The two theoretical approaches jointly provide a thorough understanding of early study success. These results have notable implications for tracking students and for further research.